Pathogenic Roles of the Carotid Body Inflammation in Sleep Apnea - Fung, Man Lung (Mediators of Inflammation, 2014)
Breathing difficulties in sleep are a hallmark of sleep-disordered breathing commonly observed in patients with sleep disorders. The pathophysiology of sleep apnea is in part due to an augmented activity of the carotid body chemoreflex. Arterial chemoreceptors in the carotid body are sensitive to inflammatory cytokines and immunogenic molecules in the circulation, because cytokine receptors are expressed in the carotid body in experimental animals and human. Intriguingly, proinflammatory cytokines are also locally produced and released in the carotid body. Also, there are significant increases in the expression of proinflammatory cytokines, cytokine receptors, and inflammatory mediators in the carotid body under hypoxic conditions, suggesting an inflammatory response of the carotid body. These upregulated cytokine signaling pathways could enhance the carotid chemoreceptor activity, leading to an overactivity of the chemoreflex adversely effecting breathing instability and autonomic imbalance. This review aims to summarize findings of the literature relevant to inflammation in the carotid body, with highlights on the pathophysiological impact in sleep apnea. It is concluded that local inflammation in the carotid body plays a pathogenic role in sleep apnea, which could potentially be a therapeutic target for the treatment of the pathophysiological consequence of sleep apnea.